2021
DOI: 10.21203/rs.3.rs-440442/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antifungal Activity of Linear and Disulfide-Cyclized Ultrashort Cationic Lipopeptides Alone and in Combination with Fluconazole Against Vulvovaginal Candida spp.

Abstract: Vulvovaginal candidiasis (VVC) occurs in over 75% of women at least once during their lifetime and is an infection that significantly affects their health. Candida strains resistant to standard azole antifungal therapy and relapses of VVC are more and more common. Hypothetically, biofilm is one of the main reasons of relapses and failure of the therapy. Ultrashort cationic lipopeptides (USCLs) exhibit high antimicrobial activities. Our previous study on USCLs revealed that disulfide cyclization can result in s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Two ultrashort cationic cyclic lipopeptides (USCLs), as previously reported (Neubauer et al, 2020), showed antibiofilm activities, wherein the mean biofilm inhibitory concentrations were 87 μg/mL (Neubauer et al, 2020). Very recently, two USCLs were reported with a minimum biofilm eradication concentration of 64 μg/mL against isolates from vulvovaginal candidiasis (Neubauer et al, 2020;Czechowicz et al, 2021). A battery of natural and synthetic peptides has been reported to suppress the biofilm's metabolic activity (Nieminen et al, 2014;Nithyanand et al, 2015).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Two ultrashort cationic cyclic lipopeptides (USCLs), as previously reported (Neubauer et al, 2020), showed antibiofilm activities, wherein the mean biofilm inhibitory concentrations were 87 μg/mL (Neubauer et al, 2020). Very recently, two USCLs were reported with a minimum biofilm eradication concentration of 64 μg/mL against isolates from vulvovaginal candidiasis (Neubauer et al, 2020;Czechowicz et al, 2021). A battery of natural and synthetic peptides has been reported to suppress the biofilm's metabolic activity (Nieminen et al, 2014;Nithyanand et al, 2015).…”
Section: Discussionmentioning
confidence: 87%
“…Frontiers in Pharmacology frontiersin.org Czechowicz et al, 2021). Appropriate combinations of antifungal agents may be helpful to overcome drug resistance; in this light, exploring the synergistic or additive effect of lipopeptides with other existing antibiotics may hold the future key (Patel et al, 2015).…”
Section: Discussionmentioning
confidence: 99%